Production and Marketing of Kolang-Kaling as a Derivative Product of Palm Fruit (Arenga pinnata) in Toisapu Hamlet, Negeri Hutumuri Ambon City - Abidin, Mayang S; Siahaya, Troice E; Tan, Lieke (Pattimura University Ambon Maluku Indonesia, 2024)
This study aimed to determine the process of processing enau into kolang-kaling and analyze the income of processing enau into kolang-kaling. The research area was defined in Dusun Toisapu, Negeri Hutumuri. The research sampling used the interview method, with a research sample of 15 members of the social forestry business group. The results showed that the stages of processing enau into kolang-kaling consisted of six stages: preparation of raw materials, separation of palm fruit, boiling, cooling, peeling, and soaking—the KUPS. Aren kolang-kaling business income analysis in April-September 2023 amounted to IDR 1.178.118 for six months of production of 168 kg, which is profitable because the ratio of total costs is IDR. 3.861.882 incurred is smaller than the total cost of revenue received IDR 5.040.000. The business can provide returns in the form of more significant income for the KUPS kolang-kaling marketing system, from producers to consumers.